Acute N-methyl-D,L-aspartate administration stimulates the luteinizing hormone releasing hormone pulse generator in the ovine fetus - Bettendorf, Markus; Zegher, F. de; Albers, N.; Hart, C. S.; Kaplan, S. L.; Grumbach, M. M. (Hormone research, 1999)
To assess whether fetal luteinizing hormone releasing hormone (LH-RH) neurosecretory neurons have the capacity to respond to an exogenous stimulus, a synthetic excitatory amino acid analogue, N-methyl-D-L-aspartate (NMDA; 15 mg/kg), was given rapidly intravenously to 8 chronically catheterized fetuses (130-142 days of gestation; term 147 ± 3 days). All 8 fetuses exhibited a rise in plasma ovine luteinizing hormone (oLH) and ovine follicle-stimulating hormone (oFSH) within 5 min. The mean maximal increments of oLH (2.25 ± 0.36 ng/ml) and oFSH (1.21 ± 0.32 ng/ml) were significantly greater than in 6 normal saline-injected controls (oLH p < 0.0002; oFSH p < 0.03). The secretion of ovine prolactin (oPRL) and ovine growth hormone (oGH) was unaffected. LH-RH (5 μg) evoked a greater oLH response (p < 0.0009) and a greater oFSH response (p < 0.03) than NMDA (n = 6). Desensitization of the fetal gonadotrope by a potent LH-RH agonist, D-Trp6Pro9NEt-LH-RH (10 μg/day i.v. × 4 days), abolished the fetal oLH and the oFSH response to NMDA (n = 5). Moreover, D,L-2-amino-5-phosphonovalerate, a specific competitive antagonist for the NMDA receptor, completely inhibited the fetal oLH and oFSH response to NMDA, whereas D-L-2-amino-5-phosphonovalerate alone did not affect the plasma oLH or oFSH levels, the gonadotropin response to LH-RH, or the release of oGH or oPRL (n = 3). In primary ovine fetal pituitary cell cultures, NMDA (10-10 to 10-6 M) had no effect on oLH, oFSH, oGH, or oPRL secretion, whereas LH-RH stimulated oLH (10-8 M; p < 0.0004) and oFSH (10-8 M; p < 0.0001) release, evidence that NMDA did not have a direct pituitary effect. The results suggest that NMDA induces oLH and oFSH secretion by stimulation of the fetal LH-RH pulse generator and is mediated by central NMDA receptors. Fetal LH and FSH secretion and the response to LH-RH decrease in late gestation in the ovine and human fetus. The relative importance of sex steroid dependent and sex steroid independent central nervous system inhibition in this developmental change is unclear. It appears that central neural inhibition in addition to sex steroid negative feedback contributes to the decrease in fetal gonadotropin concentrations in late gestation. NMDA did not affect fetal oGH or oPRL secretion.